ADVANTAGES OF THE USE AND PROTECTION OF SUBSOIL RESOURCES (World Economics and Finance Bulletin, 2025)
This article analyzes the dynamics of tax revenues from the use of subsoil resources in Uzbekistan during 2020–2024, as well as their distribution across key sectors. In particular, the shares of the mining and metallurgy industry, the oil and gas sector, and the construction materials industry are examined. The study highlights the role of subsoil tax in ensuring fiscal stability and its impact on economic growth. Furthermore, the positive outcomes of reforms such as the digitalization of tax administration, simplification of licensing procedures, and alignment with international standards are discussed. The author also develops practical recommendations aimed at improving the methodology of taxation on the use of subsoil resources.
Keywords: Subsoil; subsoil use; tax policy